Exploring sleep in farmed ungulates: A scoping review protocol - Gustavo Dias; Emma Ternman; Kathryn Proudfoot (PLoS ONE, 2026)
Sleep is essential to the life of all animals and has been broadly studied in humans and laboratory animals, although less explored in other species. Sleep may influence various aspects of an animal’s welfare, including their health, behaviour and mental states. Some researchers have begun to investigate sleep in farmed ungulates, including the role that sleep may play in animal welfare. This protocol aims to outline the methods of a scoping review aimed at describing sleep studies in farmed ungulates. The proposed scoping review aims to 1) map existing studies on sleep in farmed ungulates, 2) explore the animal welfare implications of this sleep research, and 3) identify knowledge gaps in need of future research. The PRISMA-P guidelines extension for scoping reviews will be followed, and the data will be made publicly available at the time of publication. A search will be performed in three databases: CAB Abstracts, PubMed, and Scopus. Articles will be screened using Covidence software and included if they measured sleep in species of farmed ungulates. The results will be reported using a descriptive synthesis of published sleep studies in farmed ungulates, including a timeline of when studies were published, the species and other characteristics of animals included, methods used to estimate sleep, and how sleep related to animal welfare outcomes.